Contents of phytochemicals and antinutritional factors in commercial protein-rich plant products. Issue 4 (22nd October 2018) - Mattila, Pirjo H; Pihlava, Juha-Matti; Hellström, Jarkko; Nurmi, Markus; Eurola, Merja; Mäkinen, Sari; Jalava, Taina; Pihlanto, Anne
Abstract: Objectives: The goal of this study was to determine several beneficial and antinutritional compounds in the commercial products of some protein-rich crops. Materials and Methods: Samples of faba bean ( Vicia faba ), lupin ( Lupinus angustifolius ), rapeseed press cake ( Brassica rapa/napus subsp. Oleifera), flaxseed ( Linum usitatissimum ), oil hemp seed ( Cannabis sativa ), buckwheat ( Fagopyrum esculentum ), and quinoa ( Chenopodium quinoa ) were purchased from the grocery stores and from the producers. The phytochemicals were analyzed using various validated methods. Results: Rape seed press cake contained the highest contents of phenolics. The highest contents of proanthocyanidins were found in faba bean (470 ± 14 mg/100g DW). Secoisolariciresinol-diglucoside content in the flaxseeds was 138 ± 32 mg/100 g DW and the lignanamide content of hemp seeds was 77 ± 22 mg/100 g DW. The content of phytic acid in rapeseed cake, hemp seed and flaxseed samples was 3.9 ± 0.1, 3.5 ± 0.2, and 1.9 ± 0 g/100 g DW, respectively. Rape seed cake contained glucosinolates 2.08 ± 0.74 umol/g DW and faba bean contained vicine and convicine 0.77 ± 0.11 and 0.42 ± 0.02 g/100 g DW, respectively. Quinoa contained saponins 557 mg/100 g DW and after abrasive milling/pearling the content was 36 mg/100 g DW. Generally, the phytochemicals were concentrated in the outer shell of the seed. Inhibitory activities against proteolytic enzymes, trypsin and α-chymotrypsin, varied among the samples analyzed. Highest activity was found in buckwheat samples, whereas lupin and rapeseed press cake had no inhibitory activity against tested enzymes. Conclusions: This paper presented new findings on the contents of phytochemicals in various under-used plant protein sources.